Recognition of the DNA Minor Groove by Thiazotropsin Analogues. Issue 13 (16th July 2014) - Alniss , Hasan Y.; Salvia, Marie‐Virginie; Sadikov, Mykhailo; Golovchenko, Igor; Anthony, Nahoum G.; Khalaf, Abedawn I.; MacKay, Simon P.; Suckling, Colin J.; Parkinson, John A.
Abstract Solution‐phase self‐association characteristics and DNA molecular‐recognition properties are reported for three close analogues of minor‐groove‐binding ligands from the thiazotropsin class of lexitropsin molecules; they incorporate isopropyl thiazole as a lipophilic building block. Thiazotropsin B (AcImPyiPrThDp) shows similar self‐assembly characteristics to thiazotropsin A (FoPyPyiPrThDp), although it is engineered, by incorporation of imidazole in place of N‐methyl pyrrole, to swap its DNA recognition target from 5′‐ACTAGT‐3′ to 5′‐ACGCGT‐3′. Replacement of the formamide head group in thiazotropsin A by nicotinamide in AIK‐18/51 results in a measureable difference in solution‐phase self‐assembly character and substantially enhanced DNA association characteristics. The structures and associated thermodynamic parameters of self‐assembled ligand aggregates and their complexes with their respective DNA targets are considered in the context of cluster targeting of DNA by minor‐groove complexes.